Literary Reception of Arabic Language and Literature Students Towards the Song Hub wa Hayaat (Literary Reception Study) - Nita Arianti; Khaerun Nisa Nuur, S.S., M.Pd.I; Athifah Maulidah Yusuf, S.Pd.; Dr. H. Muhsin, M.Ag. (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
This study discusses the literary reception of students majoring in Arabic Language and Literature at UIN Alauddin Makassar towards the song Hub wa Hayaat. This study uses a literary analysis approach and refers to the reception theory proposed by Wolfgang Iser. The song Hub wa Hayaat is a song popularized by Baraa Masoud. This study focuses on two main issues, namely what elements are contained in the song “Hub wa Hayaat” and what effects the song has on listeners after hearing it. This study is a field research study with a qualitative narrative approach, and the main source of data in this study is interview data. The data collection method used was interviews, and the data processing techniques were data selection, data transcription, data interpretation, and conclusion drawing. The data analysis used was descriptive analytical analysis. The results of this study indicate that the reception of the elements of feeling contained in the song Hub wa Hayaat include various elements: happy, calm, enthusiastic, peaceful, and sad. The reception of the effects that arise after listening to the song Hub wa Hayaat include the following: happy, calm, enthusiastic, peaceful, and sad. The results of this study indicate that the reception of the elements contained in the song Hub wa Hayaat includes various elements, such as happiness, calmness, enthusiasm, peace, and sadness. The researcher hopes that this study can serve as a source or reference for future researchers and provide additional scientific understanding regarding the concept of literary reception theory.